Investigation of path loss models for mobile communications in Malaysia - Chebil, Jalel; Laws, Ali K.; Islam, Md. Rafiqul; Zyoud, Al-Hareth (INSI Publications, 2011)
The design of a propagation path loss model requires knowledge of environment characteristics. Quite a number of propagation path loss models for mobile radio communication system were published in the literature. However, choosing the most suitable model for a given geographical and morphographical area is not a simple task because descriptions of terrain and land-use information can vary widely from country to country. Furthermore, Efficiency of present path loss models suffers when they are used in the environment other than for which they have been designed. The Malaysian geographical and morphographical area varies widely from areas where most models were developed. In addition, several studies in Malaysia, Indonesia and others have shown that the known path loss models perform unsatisfactory when compared with measured data. Hence, this prompts the necessity to investigate the models that suit the Malaysian environment conditions. To investigate the path loss models, measurements of path loss were carried out at an international Islamic university Malaysia. The measured path losses were compared with various path loss prediction models. The results were used to evaluate the accuracy for these models to determine the one that best fit Malaysian environment. The results show that log-normal and lee models were the closest to the measured data.